Electron-microscopic study on structural changes of mini-implants following fixed orthodontic treatment - Nadine Diku; Irina Zetu; Cristina Molnar; Doina Ghercic; Mahmoud ElSaafin; Dan Biris; Mariana Pacurar (Amaltea Medical Publishing House, 2022)
In today's society, patients who turn to the orthodontist want final results in the shortest possible time, with maximum emphasis on smile aesthetics, dental alignment and facial harmony. In this regard, some procedures have emerged to accelerate the movement of teeth through the alveolar bone, thus shortening the duration of active treatment: corticotomy, application of mini-implants, etc. Of these methods, bone anchorage on mini-implants is increasingly popular among adult patients, as it is a versatile technique that ensures a stable, bony anchorage and more predictable final results. Compared to implantology in prosthodontics, which has a long history, mini- orthodontic implants emerged later in medical practice. In 1998, Shapiro and Kokich described for the first time the possibility of using dental implants for anchorage in orthodontic therapy. Odman J et al. (Upsala University, Sweden) applied implants to patients with partial edentulousness. The results were favorable, leading the authors to recommend the technique for adult partial edentulousness. Kanomi (1997) showed that a 1.2 mm diameter titanium mini- implant provides anchorage for the intrusion of the lower front teeth. After 4 months, the mandibular incisors were intruded by 6 mm without root resorption. Birte Melsen et al. (1998) introduced the use of zygomatic ligatures as anchorage in patients with partial edentulousness. To this they attached nickel-titanium springs for intrusion and retraction of maxillary incisors. Hugo de Clerk (2008) used 4 mini-implants (Bollard type) inserted into the infra-zygomatic crest in patients with Angle class III anomalies. He used 2 mini-implants with hooks in the chin area, and patients wore Class III 150 grams elastics on each side. This direct anchorage also has orthopedic effects, with clinicians achieving upper jaw advancement and correction of mandibular prognathism.